Massive Haematochezia due to Splenic Artery Bleeding into the Colon: Unusual Manifestation of Advanced Pancreatic Cancer. (12th January 2023) - Sguinzi, R.; Pugin, F.; Bader, C.; Meyer, A.; Buhler, L.; Widmer, L.; Staudenmann, D.; Egger, B.
Abstract : We describe a case of an uncommon early pancreatic cancer presentation in a patient in his 60s who had haemorrhagic shock from extensive haematochezia and required blood transfusions as well as surveillance in an intensive care unit. A splenic artery pseudoaneurysm that had been effectively embolized by angiography was seen to be actively bleeding into the colon lumen on a computerized tomography (CT) scan along with a necrotic mass of the pancreatic tail. A pancreatic mucinous adenocarcinoma was diagnosed by a transgastric biopsy. A pancreatico-colic fistula was discovered by CT scan after a colic contrast enema. A transabdominal drainage of the necrotic collection and targeted antibiotic treatment had been performed with a satisfying patient outcome. In order to assess a potential secondary surgical resection, systemic chemotherapy was planned. In conclusion, haematochezia with hemodynamic instability originated from a splenic artery pseudoaneurysm fistulising into the colon (arterio-colic fistula) and sepsis originating from a tumoral pancreatic abscess fistulising into the colon (tumoral pancreatico-colic fistula).